Welfare, choice, and solidarity in transition : reforming the health section in Eastern Europe - Kornai, János (Federico Caffè lectures., 2001)
Reform of the welfare sector is an important yet difficult challenge for all countries in transition from socialist central planning to market-oriented democracies. Here a scholar of the economics of socialism and post-socialist transition and a health economist take on this challenge. This 2001 book offers health sector reform recommendations for ten countries of Eastern Europe, drawn consistently from a set of explicit guiding principles. After discussing sector-specific characteristics, lessons of international experience, and the main set of initial conditions, the authors advocate reforms based on organized public financing for basic care, private financing for supplementary care, pluralistic delivery of services, and managed competition. Policymakers need to achieve a balance, both assuring social solidarity through universal access to basic health services and expanding individual choice and responsibility through voluntary supplemental insurance. The authors also consider the problems that undermine effectiveness of market-based competition in the health sector.